UNIFIED ITALY, SOUTHERN WOMEN AND SEXUAL VIOLENCE: SITUATING THE SEXUAL ASSAULT TV “PRANK” AGAINST EMMA MARRONE WITHIN THE DYNAMICS OF CONTEMPORARY ITALY AS A SCOPIC REGIME - Messina, Marcello; Di Somma, Teresa (TROPOS: COMUNICAÇÃO, SOCIEDADE E CULTURA (ISSN: 2358-212X), 2017)
ABSTRACT On 22 April 2017, while rehearsing a musical performance for talent show “Amici di Maria De Filippi”, female singer Emma Marrone was repeatedly molested and groped by a male dancer as part of a prank orchestrated by the TV team. During the broadcast, cast members and guest stars laughed at Marrone’s irritated reactions to the “simulated” sexual assaults of the dancer. The episode was then normally broadcast and promoted as a hilarious prank. While totally partaking in the general indignation and outrage that this episode has brought about in international media and in national anti-abuse organisations, we want to focus on Marrone’s positionality as a diasporic Southern Italian woman, which has largely gone overlooked in the diffused reactions to the episode. In this work, we proceed to unearth the often-silenced histories of mass rapes against Southern women committed during the Italian Unification period and in the final stages of World War II, in order to expose the exploitation of female bodies as military trophies, perpetrated by occupying (Italian and international) forces. We then situate the episode involving Emma Marrone and “Amici di Maria de Filippi” within the perverse dynamics of contemporary Italy as a scopic regime that claims continuity with these histories of racialised sexual violence. RESUMO No dia 22 de abril de 2017, enquanto ensaiava uma performance musical para o show de talentos “Amici di Maria De Filippi”, a cantora Emma Marrone foi repetidamente molestada e tocada por um dançarino, como parte de uma brincadeira orquestrada pela equipe do show. Durante a transmissão, membros do elenco do programa, assim como artistas convidados, riam das reações irritadas de Marrone às moléstias “simuladas” do dançarino. Além de participar totalmente na indignação que esse episódio gerou na mídia internacional e nas organizações nacionais anti-abuso, queremos chamar a atenção para a posição de Marrone como mulher diaspórica do Sul da Itália, uma caraterística que ficou geralmente negligenciada no contexto das reações ao episódio. Nesse artigo, pretendemos desenterrar histórias silenciadas de estupros de massa contra as mulheres sulistas, perpetrados durante a Unificação Italiana e no final da Segunda Guerra Mundial: faremos isso para denunciar a exploração de corpos femininos como troféus militares por parte de forças ocupantes, tanto internacionais quanto italianas. Em seguida, situaremos o episódio que envolveu Emma Marrone e “Amici di Maria De Filippi” dentro das dinâmicas perversas da Itália contemporânea, entendida como regime escópico que reivindica a própria continuidade com essas histórias de violência militar sexualizada e racializada.